Differentiated Slip Casting: Producing Variable Thickness Ceramic Tiles with Functionally Graded Plaster Moulds - Efilena Baseta; Marco Palma; Florian Heher; Thomas Konegger; Martin Kaftan (Ceramics)
This paper introduces a method that enhances the traditional slip casting technique’s potential to fabricate ceramic objects with variable thickness. The variability depends on the different filtration rates offered by plaster moulds of varying densities. Two sets of experiments are presented. They focused on identifying (1) the maximum workable density range of moulds made from plaster of Paris and (2) the range of thickness in the resulting ceramic casts. This was accomplished by creating four square flat moulds with different gypsum/water (G:W) ratios and their corresponding casts. Based on these findings, the second set of experiments focused on assembling graded plaster moulds with variable densities (G:W 1:3 to 2:1), resulting in ceramic tiles exhibiting a thickness gradient of 2 mm. These results suggest the possibility of producing double-curved ceramic objects (e.g., custom ceramic tiles or sanitaryware) with graded thickness, tailored to their desired structural and functional performance.